ALIH TUTUR DALAM WACANA INTERAKSI KELAS DI SMP - Heri Susanto (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
The aims of this research is to describe turn taking pattern, adjacency pair, and transition relevance place (TRP). The research used qualitative descriptive method. Data were collected using observation and selected from the classroom interaction at the 9B graders of SMPN 2 Sambungmacan, Sragen on November 2015. The result of analysis showed that turn taking pattern followed talk shift systematically where teacher role was the initiator. Adjacency pair pattern followed 5 of 8 rules so it could not always be applied in conversation. In TRP, it applied a rule where teacher let students respond. If responses were not applicable, teachers let other turns delivering instruction and information.